Peran ASEAN Strategic Plan for Culture and Arts dalam Mendorong Identitas Regional Asia Tenggara - Rohman, Dede; Bandau, Praycillia Jovanka (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2025)
The ASEAN Strategic Plan for Culture and Arts (ASPCA) 2016–2025 was initiated to address the relatively low level of socio-cultural cohesion in Southeast Asia compared to its political and economic integration, as well as the pressures of globalization that threaten local cultural values. This article aims to analyze the role of ASPCA as a cultural soft power instrument in fostering regional identity and strengthening socio-cultural integration within ASEAN. The study is grounded in the theoretical framework of soft power and new regionalism, which emphasizes the construction of regional identity through social interaction, cultural exchange, and the involvement of state and non-state actors. Using a qualitative descriptive approach, this research employs document analysis of official ASEAN policy documents, academic literature, and reports from relevant international organizations. The findings show that ASPCA contributes to the formation of a shared regional identity by promoting cross-border cultural collaboration, strengthening awareness of cultural heritage, facilitating intercultural dialogue, and integrating ASEAN values into educational and community-based programs. However, the implementation of ASPCA still faces challenges, including disparities in institutional capacity, political priorities, and resource availability among member states. Overall, this study argues that ASPCA places culture as a substantive pillar of ASEAN integration, complementing political and economic dimensions, and highlights the strategic role of culture in advancing ASEAN’s legitimacy and cohesion in the global arena.